(untitled) (Research, Society and Development, 2024)
Introduction: The management of stab wound trauma is a critical concern in emergency services due to its potential severity and complexity. Rapid identification and appropriate treatment are essential to improve patient outcomes. Objective: This article reviews current literature on best practices for managing stab wound trauma in emergency settings, highlighting effective interventions and treatment strategies. Method: A systematic literature review was conducted using databases such as PubMed, Google Scholar, and Scopus. Studies published in the last ten years addressing penetrating trauma management in emergency settings were included. Discussion: Literature emphasizes the importance of well-defined protocols, such as Advanced Trauma Life Support (ATLS), to guide initial treatment. Rapid assessment and hemorrhage control are crucial. Interventions like fluid resuscitation and blood transfusion are often necessary. The decision between immediate surgical intervention versus careful observation depends on patient stability and wound location. Conclusion: Effective management of stab wound trauma in emergency settings requires a multidisciplinary approach and well-established protocols. Continuous training of healthcare professionals is essential to ensure the proper implementation of best practices.